Identifying and Understanding the Language Curriculum Across the World - Ferrer, Christine N.; Somera, Aubrey S. (Center of Language and Cultural Studies [CLCS], 2022)
This article compares and contrasts the Language Curriculum in the United States, United Arab Emirates, Mongolia, Philippines and Indian Language Curriculum for the year 2022. This is a comparative analysis; a research journal conducted to analyze the ideological, cultural, and political-economic elements that impact the development of language curricula in five different countries. Furthermore, the educational goals and ideologies that underpin both curricula are discussed. A very intriguing conclusion emerges when considering the curricula's unspoken aims. All the five (5) nations' language and literature curricula emphasize the significance of citizenship and character education and are interwoven into curricula instruction. Meanwhile, the US language curriculum prioritizes creating American identity, with a focus on improving learning for the professional workforce and career-ready persons, which will help the global economy in the future. Meanwhile, moral and religious training is prioritized in the United Arab Emirates, Mongolia, Philippines and Indian language curriculum. Language education or curriculum are intertwined in nation-building. After examining, comparing, and contrasting both curricula, the author discovered that the US successfully instills character education to mold the worldview and characteristics of its population derived from their clear ideology, whereas the United Arab Emirates, Mongolia, Philippines and India are rather unexplained and ambiguous. As a result, this article demonstrates that there is an opportunity for development for educators and educational leaders in the United Arab Emirates, Mongolia, Philippines and India to be more explicit in determining which character is best exposed in the language curriculum.